Analysis of Land Cover Changes to Increase Land Surface Temperature in Surabaya using Landsat Satellite - Prayuda, Shanas Septy; Kusuma, Maritha Nilam (Pusat Penelitian dan Pengembangan BMKG, 2023)
Surabaya has experienced very significant development in the last few decades. Changes in land use will cause the Urban Heat Island phenomenon. This study aims to determine how far the impact of land cover changes on the increase in surface temperature in the Surabaya. The use of Landsat satellite imagery is considered very effective in describing land cover and surface temperature because it has good spatial resolution and long data availability. During 1991 – 2020 there was a significant decrease in the amount of vegetation by 24.3%, decrease in the number of water bodies by 4.9%, and increase in the number of buildings by 29.2%. The average increase in Land Surface Temperatures was 1.40°C between decades 2 and 1, and an increase of 2.19°C between decades 3 and 2. The development of Surabaya began in the city center and then developed mainly in the west and east. The urban development model is consistent with the pattern of land surface temperature changes. Each type of land cover has special characteristics on the value of NDVI, NDBI, and surface temperature. Changes in cover from water bodies to buildings have the highest contribution to increasing the and surface temperature. There was a significant increase in hotspots in decade 3 in Surabaya which indicated an increasingly severe UHI phenomenon.